Design and development of flexible boards and their application to biomedical engineering - José Luis Ordoñez-Ávila; Luis Eduardo Martínez Osorto; Fernanda Cáceres Lagos (Tecnología en Marcha)
Wearable devices in the healthcare industry require to be easy to use, comfortable to handle, and reliable in their operation. This article presents a study on the design and manufacture of flexible circuits and their applications in the field of biomedical engineering. The methodology used in this study is the incremental methodology, which implies a step-by- step approach of the design and fabrication process. The study focuses on the fabrication of a flexible circuit using conductive ink and a flexible substrate. The results showed that the Voltera V-ONE printer can be used to create these circuits with a high accuracy and precision. Various substrates were used for the testing process due to their different characteristic. The final circuit was tested and found to be functional for applications in biomedical engineering.